G Guest Guest Oct 2, 2005 #1 x + 5(7x + 2) = 12x + 2(x + 1) – 3 x+35x+10=12x+2x+2-3 36x+10=14x+2-3 36x+10=14x-1 -14x -14x 22x+10=-1 -10 -10 22x=-11 22 22 x=-1/2 Correct?

x + 5(7x + 2) = 12x + 2(x + 1) – 3 x+35x+10=12x+2x+2-3 36x+10=14x+2-3 36x+10=14x-1 -14x -14x 22x+10=-1 -10 -10 22x=-11 22 22 x=-1/2 Correct?

R rahidz2003 New member Joined Oct 1, 2005 Messages 25 Oct 2, 2005 #2 Yep, looks good, and if you put -1/2 back into the original equation (a good way to check), you get -18+10=-7-1 -8=-8 Since both sides are equal, -1/2 is a solution

Yep, looks good, and if you put -1/2 back into the original equation (a good way to check), you get -18+10=-7-1 -8=-8 Since both sides are equal, -1/2 is a solution